2009
DOI: 10.4049/jimmunol.0901326
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Induces Sustained Elevation of Intracellular Ca2+ in Rodent Microglia

Abstract: Microglia are intrinsic immune cells that release factors, including proinflammatory cytokines, NO, and neurotrophins, following activation after disturbance in the brain. Elevation of intracellular Ca2+ concentration ([Ca2+]i) is important for microglial functions, such as the release of cytokines and NO from activated microglia. There is increasing evidence suggesting that pathophysiology of neuropsychiatric disorders is related to the inflammatory responses mediated by microglia. Brain-derived neurotrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 66 publications
4
59
0
Order By: Relevance
“…In addition, pretreatment with BDNF suppressed the release of NO from murine microglial cells activated by IFN-␥ (5). To date, BDNF is also well known for its involvement in the pathophysiology of neuropsychiatric disorders (4,5).…”
Section: Microglia Are Immune Cells That Release Factors Including Pmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, pretreatment with BDNF suppressed the release of NO from murine microglial cells activated by IFN-␥ (5). To date, BDNF is also well known for its involvement in the pathophysiology of neuropsychiatric disorders (4,5).…”
Section: Microglia Are Immune Cells That Release Factors Including Pmentioning
confidence: 99%
“…We have reported previously that BDNF induces a sustained increase in intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) through the activation of the phospholipase C (PLC) 2 pathway in rodent microglial cells (5). We also tested the effect of 2-aminoethoxydiphenyl borate or SKF-96365, both of which can inhibit canonical transient receptor potential (TRPC) channels (6,7) and showed that sustained activation of TRPC channels occurred after a brief treatment with BDNF and contributed to the maintenance of BDNF-induced sustained intracellular Ca 2ϩ elevation (5).…”
Section: Microglia Are Immune Cells That Release Factors Including Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of these receptors by BDNF resulted in sustained [Ca 2ϩ ] i elevation, which was mediated by an initial PLC/InsP 3 -driven Ca 2ϩ release from the ER that followed by a long-lasting activation of the SOCE. Incubation with BDNF also decreased release of NO from the activated microglia (597). LPS-induced activation of microglia can trigger the expression of NGF in cultured microglial cells, which can also be induced by stimulation of A 2 adenosine receptors (366).…”
Section: Neurotrophin Receptorsmentioning
confidence: 99%
“…In response to a chemotropic factor such as netrin-1, brain-derived neurotrophic factor (BDNF), or nerve growth factor (NGF), phospholipase C (PLC) is activated [24,25], which hydrolyzes phosphatidylinositol 4,5-bisphosphate (PIP 2 ) into IP 3 and diacylglycerol. Once created, IP 3 selectively binds to IP 3 receptors (IP 3 Rs) located on the surface of the endoplasmic reticulum (ER), initiating IICR [26].…”
Section: Glossarymentioning
confidence: 99%